Encouraging understanding and respecting diversity through culture-based sociology learning - Setianingsih, Agnes Tutut (Jurnal Teori dan Praksis Pembelajaran IPS, 2024)
Culture-based education in sociology learning significantly impacts students' understanding of social diversity. Integrating cultural values in the curriculum raises students' awareness of the diversity of society, broadening their view of social reality. This research explores how a culture-based approach in sociology education can enhance students' understanding and attitudes toward social diversity and tolerance. This research used the Systematic Literature Review (SLR) method. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was used as the established procedure. The study found that implementing Culture-Based Education in sociology learning significantly impacts students' understanding of social diversity. Although there are challenges in implementing the Culture-Based Education approach, they can be overcome through holistic efforts. The impact of Culture-Based Education on the development of students' social, critical, and analytical skills is very positive. The expansion of social skills through cross-cultural interactions, the improvement of critical thinking skills, the development of social analytical skills, the linking of sociological concepts with social contexts, and the formation of critical and tolerant attitudes are all aspects that enrich students' learning experiences. This research emphasizes the importance of integrating cultural values into the curriculum to enhance students' understanding of social diversity and their ability to navigate multicultural environments. It calls on educational institutions to adopt and improve culture-based approaches. Additionally, it highlights the need to address implementation challenges and to continuously evaluate and adapt practices to foster the development of socially aware and culturally competent students.